Association of uncoupling protein (Ucp) gene polymorphisms with cardiometabolic diseases - Anna E. Pravednikova; Sergey Y. Shevchenko; Victor V. Kerchev; Manana R. Skhirtladze; Svetlana N. Larina; Zaur M. Kachaev; Alexander D. Egorov; Yulii V. Shidlovskii (BMC, 2020)
Abstract The hereditary aspect of obesity is a major focus of modern medical genetics. The genetic background is known to determine a higher-than-average prevalence of obesity in certain regions, like Oceania. There is evidence that dysfunction of brown adipose tissue (BAT) may be a risk factor for obesity and type 2 diabetes (T2D). A significant number of studies in the field focus on the UCP family. The Ucp genes code for electron transport carriers. UCP1 (thermogenin) is the most abundant protein of the UCP superfamily and is expressed in BAT, contributing to its capability of generating heat. Single nucleotide polymorphisms (SNPs) of Ucp1-Ucp3 were recently associated with risk of cardiometabolic diseases. This review covers the main Ucp SNPs A-3826G, A-1766G, A-112C, Met229Leu, Ala64Thr (Ucp1), Ala55Val, G-866A (Ucp2), and C-55 T (Ucp3), which may be associated with the development of obesity, disturbance in lipid metabolism, T2D, and cardiovascular diseases.